Factors that influence job performance in Felda Global Ventures Plantations (Malaysia) Sdn. Bhd / Muhammad Izzwan Mohd Ariff - Mohd Ariff, Muhammad Izzwan (Faculty of Business and Management, 2015)
This study is an attempt to address the factor that influence of job performance at Felda Global Ventures Plantations (Malaysia) Sdn. Bhd. There were 112 respondents from all department of Felda Global Ventures Plantations (Malaysia) Sdn. Bhd. employees. 120 questionnaires were distributed and the researcher managed to use 112 respondents for the result findings. A questionnaire was used as the main data collection method. Pearson Coefficient Correlation analysis was used to find direction and strength of correlation between each dependent and independent variables. The result analysis showed that all the independent variable has a significant relationship towards the job performance. The intrinsic motivation is shown significant towards the employee performance. Besides that, the study also shows that there is a significant relationship between extrinsic motivation and employee performance. The reason of this two IV is significant is explain in the conclusion. In order to encourage the future study in this area, the researcher stated a few recommendations. It highlighted the ideas to conduct better study in the future for the organization as well as for the future researchers.